Navigating the Shadows of Others’ Traumas: An In-Depth Examination of Secondary Traumatic Stress and Psychological Distress among Rescue Professionals - Nazia Noureen; Seema Gul; Aneela Maqsood; Humaira Hakim; Arooj Yaswi (Behavioral Sciences, 2023)
Rescue workers, who often find themselves on the frontlines of traumatic events, face an increased risk of experiencing secondary traumatic stress (STS) and psychological distress (PD). The nature of their work, alongside professional factors, can influence the way these psychological aspects manifest and their level of severity. This study aimed to explore the relationship between STS and PD in rescue workers. Additionally, it sought to understand how factors such as age, years of experience, duration of work, training received and direct exposure to trauma explain significant variations in reporting to STS. To conduct this research, a cross-sectional study design was implemented involving a sample of 80 rescue workers from the Punjab province in Pakistan. Data was collected over eight weeks using the secondary traumatic stress scale (STSS-17) and the general health questionnaire (GHQ-12) as primary assessment tools. Participants’ data was analyzed through Pearson correlation analysis, t-tests, and ANOVA. A strong positive correlation between STS and PD among rescue workers was established. Age significantly explains variation in scores, with older workers displaying reduced STS and PD symptoms. Rescue workers working for longer hours reported elevated STS compared to those working shorter shifts. Workers with more extended professional experience showcased lower STS, highlighting the potential resilience acquired over time. The study also underscored the importance of training duration: longer, well-structured training was associated with decreased STS and PD. Interestingly, longer exposure to trauma was found to be related to lower STS scores, albeit this warrants further investigation. This study underscores the intertwined nature of STS and PD among rescue workers and the various modulating factors. The study paves the way for more comprehensive research, expanding geographically and demographically.